2021
DOI: 10.3390/su13179849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flipped Learning Approaches on Students’ Learning Performance in Software Engineering Education

Abstract: Software engineering education plays an important role in keeping students educated with software technologies, processes, and practices that are needed by industries. Nevertheless, the nature of software engineering learning activities in traditional classrooms is limited in scope and time, making it more difficult to achieve a proper balance between theory and practice and address industrial demands. This makes scant provision for assisting students in keeping their software engineering knowledge current. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Hwang et al, 2019). Thus, it can be concluded that the application of the flipped learning model can have a positive effect on improving students' creative thinking skills (Lin, 2021).…”
Section: Resultsmentioning
confidence: 95%
“…Hwang et al, 2019). Thus, it can be concluded that the application of the flipped learning model can have a positive effect on improving students' creative thinking skills (Lin, 2021).…”
Section: Resultsmentioning
confidence: 95%
“…Quality teaching resources are created through the use of an online platform, and teaching methods have evolved to include a wide range of methods and strategies, as well as the creation of teaching during times of crisis. Teachers’ lectures from traditional classrooms are converted into video clips for students to see before class ( Lin, 2021 ). As a result, the flipped learning method offers both synchronous and asynchronous learning options.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, students found flipped events to be more motivating if the sessions were technology-enhanced (Dean et al, 2013). In this regard, the studies by Lin (2021) or Sangermán Jiménez et al (2021) revealed that input videos are preferred most by students for the self-study phase. Instructional videos allow students to pause the learning process and review the content as often as necessary (Suárez et al, 2021) while, in contrast, Bishop and Verleger (2013) argues that texts are usually only read superficially by students.…”
Section: Introductionmentioning
confidence: 99%